Exploring the Spatial Ability of Undergraduate Students: Association With Gender, STEM Majors, and Gifted Program Membership. (October 2017) - Yoon, So Yoon; Mann, Eric L.
Spatial ability has been valued as a talent domain and as an assessment form that reduces cultural, linguistic, and socioeconomic status biases, yet little is known of the spatial ability of students in gifted programs compared with those in general education. Spatial ability is considered an important indicator of potential talent in the domains of science, technology, engineering, and mathematics (STEM). This study explored undergraduate students' spatial ability, focusing on mental rotation, by investigating the relationships of three variables with performance on a spatial ability test, in terms of test scores and test completion time. A three-way analysis of variance revealed statistically significant main effects of gifted program participation, choice of academic major, and gender, suggesting that students who participated in a gifted program, who majored in a STEM discipline, or who were male outperformed their counterparts on a measure of spatial ability when the other conditions were equivalent. No interaction effects existed among the three variables, indicating that none of them functioned as a moderator of students' performance on the spatial ability assessment. However, when spatial ability was considered as a mediating variable in a path model, gender had the largest total effect on the probability of students majoring in a STEM area. In addition, the more time students spent on the spatial ability test, the better they tended to perform, which is a finding inconsistent with current literature.